Workplace plus : living and working in English / Joan M Saslow; Tim Collins; Barbara R Denman - Saslow, Joan M.
With a focus on valuable life skills, work skills and language, the "Workplace Plus" series prepares adults to function successfully at work and within an English-speaking community. It provides practical conversations, listening, speaking, reading and writing practice.